2004
DOI: 10.1080/00498250400005708
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation and rearrangements of flavanones by mammalian cytochrome P450

Abstract: To clarify the metabolic pathways of flavanones in mammals, the metabolism of (+/-)-flavanone and (+/-)-4'-methoxyflavanone by rat liver microsomes and recombinant human P450s in which structural changes are readily identifiable were examined. The beta-nicotinamide adenine dinucleotide phosphate (NADPH)-dependent formation of flavone plus (+/-)-2,3-trans-flavanonol and of 4'-methoxyflavone plus (+/-)-2,3-trans-4'-methoxyflavanonol, respectively, by rat liver microsomes was observed. The same metabolites were g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…2) (Breinholt et al 2002;Kagawa et al 2004). CYP1A1, CYP1A2 and CYP2B6 produce flavone, and CYP1A1 and CYP2B6 even produce isoflavone, from flavanone (Kagawa et al 2004).…”
Section: Non-plant P450s Catalyzing Flavonoid Metabolism and Catabolismmentioning
confidence: 95%
“…2) (Breinholt et al 2002;Kagawa et al 2004). CYP1A1, CYP1A2 and CYP2B6 produce flavone, and CYP1A1 and CYP2B6 even produce isoflavone, from flavanone (Kagawa et al 2004).…”
Section: Non-plant P450s Catalyzing Flavonoid Metabolism and Catabolismmentioning
confidence: 95%
“…16) In order to identify other metabolic monohydroxyflavanones, we have now developed procedures to synthetically produce these compounds and to identify them by GC-MS analysis.…”
Section: )mentioning
confidence: 99%
“…10) Recently, two interesting pharmacological properties of flavonoids have been reported. 1) The polymethoxyflavone, tangeretin, protects against the development of experimentally-induced Parkinson's disease in rats.11) 2) Other polymethoxyflavones inhibit the cellular excretion of certain drugs-a process mediated by P-glycoprotein.12,13) Cytochrome P450s can remove a flavonoid C-4Ј methyl and can add a hydroxyl at the C-3Ј position.14,15) To understand the diverse pharmacological effects of dietary flavonoids, their metabolic pathways must be known.A previous study of ours 16) showed that both rat and human cytochrome P450s convert flavanones to the corresponding 2,3-trans-flavanonols and flavones; whereas, only the human enzyme can convert the flavanone to isoflavone. We also recently reported a procedure for the specific deuteration of flavanones.…”
mentioning
confidence: 99%
See 2 more Smart Citations